Beriberi Outbreak Among Unauthorised Immigrants in a Detention Camp in Malaysia - Sunita Abdul Rahman; Mohammad Saffree Jeffree; Fadzilah Kamaludin; Intan Azura Din; Mahanim Yusof; Kamruddin Ahmed (2018)
In February 2012, a district health authority received three inmates with bilateral leg swelling and difficulty in breathing from a detention camp for unauthorized immigrants. A case control study was conducted. Fasting blood samples of case and control groups were collected according to instructions of the laboratory for determining thiamine level, and their 1 week dietary intake was analyzed. 9% (21/226) of inmates had bilateral leg swelling, and 75% (6/8) of them had low thiamine level (< 66 mmol/L). Their diet contained mainly polished rice and other items with low thiamine contents. Bilateral leg swelling was associated with history of no meat consumption during past 3 months (OR 8.4; CI 2.2–32.1). Patients were treated with 100 mg thiamine intravenously and 5 mg orally per day for 6 weeks. All patients responded well. The management was advised to provide vitamin B complex daily, and encouraged to provide thiamine rich foods.